Perbedaan Berat Badan Bayi dan Hormon Prolaktin Dengan Breast Care Pada Ibu Nifas Normal (Studi di RSU Sarila Husada Kabupaten Sragen) - Winnie Tunggal Mutika; Ari Suwondo; Runjati Tangwun (Berita Kedokteran Masyarakat (BKM), 2018)
Effect of breast care among postpartum women on baby weight and prolactin hormones: preliminary studyPurposeThe aim of this study was to assess effectivity of breast care among postpartum women on baby weight and prolactin hormones.MethodThe study used quasi experimental with non equivalent time samples design. The sample was postpartum women in Sarila Husada hospital, Sragen and the sampling was performed by purposive sampling. The analysis was bivariate analysis using a paired t-test.ResultsThe average baby's weight before breast care was 3.1 kg with a standard deviation of 0.3. After breast care the average baby's weight was 3.0 kg with a standard deviation of 0.2. Statistical test obtained a p-value of 0.024, thus there was a significant difference between baby's weight before and after breast care. The average of prolactin hormone before breast care was 66.4 ng/ml with a standard deviation of 15.2. After breast care, the average prolactin hormone was 112.1 ng/ml with a standard deviation of 21.0. Statistical test obtained a p-value of 0.000, thus there was a significant difference between prolactin hormone before and after breast care.ConclusionThere were significant differences in baby weight with a decrease of 2.2% and prolactin hormone with an increase of 72.1% before and after breast care in postpartum women. In the breast care group, baby’s weight decreased by 2.2% but the baby’s weight loss did not exceed the maximum baby’s weight loss in the first week at 7%.